(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2014)
Objective: To determine the prognostic factors of the functional outcome of patients surgically treated for acute extradural haematoma. Methods: Sixty three cases of extradural haematoma was studied over a period of two years from July 2001 to July 2003 in dept of neurosurgery Dhaka Medical college & Hospital. Study was prospective for their clinical profile and operative measures. Clinical characteristics, radiologic findings, and the time intervals with regard to treatment course were investigated to determine the interactions between all these factors and functional outcome. Their clinical presentation varied from intense headache to deep coma and fixed pupil. Patients were divided into two groups on the basis of the GCS level on admission and also on the basis of the operative time interval. All patients were treated surgically and haematoma evacuated. Results: Out of 63 cases 26 cases (41.3%) were in 3rd decade. Male to female ratio was 14:1, where males were 93.6% (59 cases) out of total 63. Most common mode of injury causing EDH was due to RTA 57% followed by assault (26.9%) & fall from height (15.8%). CT scan confirms site of EDH which was more common in temporal region in 26 cases(41.2%) followed by frontal 13 cases (20.6%), parietal 11 cases (17.4%), temporoparietal region 10 cases (15.8%)& occipital region 3 cases(4.76%). The mean interval between injury and operation in two groups were 36 hours & 5 days(Av). Most important finding was the operative outcome where mortality was 30.1%.This mortality was dependent on the GCS level rather than the preoperative time. But the number of patients achieved good recovery (resume normal life GOS 5) was significantly more among them who were treated within 3 days (mean 24.15 hours) than those who were treated within 5.26 days . Conclusion: This study identifies the risk factors involved in the functional outcome of patients who underwent surgical treatment for acute epidural hematomas. Excessive delay occurred in recognizing the condition and in subsequent transfer of patients. Early intervention in traumatic EDH cases should not be delayed. It gives not only the better result but also reduces the number of disabled vegetative person and reduces morbidity and above all reduces social burden, hospital staying and cost. DOI: http://dx.doi.org/10.3329/jpsb.v1i2.19522